Uzbekistan’s Cotton Export Competitiveness in China (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This Article provides Uzbekistan’s cotton export competitiveness in Chinese market over the years 2007-2017. Balassa comparative advantage index is used to analyze competitiveness for cotton products. The results show that cotton export of Uzbekistan to China had fluctual trend between 2007 and 2017 years. In 2008, an export value of cotton of Uzbekistan reached to top, consisting of 84 percent of total export. Based on investigations, it confirms that competitiveness of Uzbek raw cotton export in the Chinese market minimized over the decade. Meanwhile, non-retail pure cotton yarn export kept increasing. Because of economic and agricultural policy, Uzbekistan has been paying more attention on reprocessing of raw cotton and maximizing the volume of finished cotton products. However, Uzbekistan keeps one of the major cotton exporters to China up to now. This research learns some significant points to develop the competitiveness of Uzbekistan’s cotton products export on the Chinese and global markets.